Educating for durable solutions : histories of schooling in Kenya's Dadaab and Kakuma refugee camps - Monaghan, Christine (Lecturer in international education) (New York : Bloomsbury Academic, 2021)
"Educating for Durable Solutions considers the challenges of providing access to quality education for refugees trapped in protracted situations (PRS). Using United Nations High Commissioner for Refugees (UNHCR) archival documents and interviews with refugees, policymakers and program officers, Christine Monaghan reconstructs the contemporary education histories of two of the world's largest refugee camps, Kenya's Dadaab and Kakuma camps. Monaghan goes on to comparatively analyze changes to refugee education globally and in the camps and makes proposals for how the international community could tackle future emergency challenges. The research findings and proposals go against the grain of conventional thinking about refugee education by arguing that "the state" still matters"--
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Refugees -- Education -- Kenya; Refugee camps -- Kenya; Réfugiés -- Éducation -- Kenya; Refugee camps; Refugees -- Education; Kenya